Brand Empowerment Workshop boosts UMPSA’s Visibility - Naqiah, Puaad (UMPSA, 2024)
GENTING HIGHLANDS, 3 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised a Brand Empowerment Workshop, serving as a platform to analyse the impact of branding changes on the identity and image of the university involving stakeholders, particularly alumni, industry, students, and the community.